العلاقة بين رغبة الطالبات في تعلم اللغة العربية وقدرتهن في مهارة القراءة للصف الثامن المتوسطة في المدرسة أولو النهى ميدان جوهر سومطرة الشمالية (بحث علاقي) - Zahirah, Amida; Tiy Kumarrabbi Karo, Tiy Kumarrabbi Karo; Muhammad Sapii, Muhammad Sapii (Cahaya Ilmu Bangsa Institute, 2025)
ABSTRACT : The formulation of the problem in this research is whether there is a relationship between students' interest in learning Arabic and reading ability in Class VIII of Ulun Nuha Islamic Middle School Medan Johor, North Sumatra? This research aims to determine the relationship between students' interest in learning Arabic and reading ability in Class VIII of Ulun Nuha Islamic Middle School, Medan, Johor, North Sumatra. The method used is a quantitative approach with a correlation method. The technique used to find research results is using statistical data with the Product Moment formula with a population and sample of 34 people. And the results of this research show that there is a relationship between students' interest in learning Arabic and reading ability in Class VIII of Ulun Nuha Islamic Middle School, Medan, Johor, North Sumatra. With an r_xy value of 0.450, this figure shows that there is a relationship between the two variables which has a medium value in a positive direction. So the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The conclusion is that there is a moderate relationship between the two variables. Keywords: Students' Interest in Learning; Arabic; Reading Skills; تجريد سؤال البحث: هل هناك العلاقة بين رغبة الطالبات في تعلم اللغة العربية وقدرتهن في مهارة القراءة للصف الثامن المتوسطة بالمدرسة أولو النهى ميدان جوهر؟ وهدفه لمعرفة علاقة بين رغبة الطالبات في تعلم اللغة العربية و قدرتهن في مهارة القراءة للصف للصف الثامن المتوسطة في المدرسة أولو النهى ميدان جوهر سومطرة الشمالية. والمنهج المستخدم هو المنهج الكمي بالنوع العلاقي وطريقة تحليل البيانات المستعملة هي طريقة إحصائية بالرمز علاقة ضرب العزم (product Moment) وكان مجتمع البحث وعينته 34 شخصا. والنتيجة من هذا البحث أن نتيجة العلاقة بين رغبة الطالبات في التعلم وقدرتهن على مهارة القراءة للصف الثامن المتوسطة في المدرسة أولو النهى ميدان جوهر سومطرة الشمالية هي بقيمة معامل الارتباط 0,450 والعلاقة معتدل بنفس الاتجاه. وعرفت أن الفرضية التبادلية (Ha) مقبولة والفرضية العدمية (Ho) مردودة. والأخير، عرفت أن فيه وجود العلاقة بين المتغيرتين. كلمة المرور: رغبة التعلم، اللغة العربية، مهارة القراءة.